Investigation on the Effects of the Formation of a Silver “Flower-Like Structure” on Graphene - Zakaria, Rozalina; Yusoff, S.F.A.Z.; Law, K.C.; Lim, C.S.; Ahmad, Harith (SpringerOpen, 2017)
In this report, we experimentally investigate the formation of “flower-like silver structures” on graphene. Using an electrochemical deposition technique with deposition times of 2.5 and 5 min, agglomerations of silver nanoparticles (AgNPs) were deposited on the graphene surfaces, causing the formation of “flower-like structures” on the graphene substrate. Localized surface plasmon resonance (LSPR) was observed in the interaction between the structures and the graphene substrate. The morphology of the samples was observed using a field-emission scanning electron microscope (FESEM) and Raman spectroscopy. Thereafter, the potential of the flower-like Ag microstructures on graphene for use in Raman spectroscopic applications was examined. The signal showed a highest intensity value after a deposition time of 5 min, as portrayed by the intense local electromagnetic fields. For a better understanding, the CST Microwave Studio software, based on the finite element method (FEM), was applied to simulate the absorption characteristics of the structures on the graphene substrate. The absorption peak was redshifted due to the increment of the nanoparticle size.